Numerical Study of Airflows, Thermal Structures, and Performance in a Circular Tube Heat Exchanger with Staggered Combined Vortex Producers - Amnart Boonloi; Withada Jedsadaratanachai (Journal of Engineering, 2024)
A numerical investigation is conducted into the airflow topologies and thermal structures of a circular tube heat exchanger (CTHX) fitted with combined vortex producers (CVP), including winglets and V‐profile ribs. The CVP installation is necessary to produce vortex flows in the CTHX, which bounce over the CTHX wall, significantly altering the thermal boundary layer. This change affects the local convective heat transfer coefficient and heat transfer rate. Moreover, producing vortex flow can improve air mixing quality, further augmenting the heat transfer rate and thermohydraulic efficiency. The effects of CVP heights ( b 1 / D and b 2 / D ), CVP types ( X ‐1, X ‐2, and Y ), and airflow directions on flow topology and thermal structure are considered. The airflow velocity, in terms of the Reynolds number from 100 to 2000 (considered from the entry settings), is examined. The current numerical challenge is resolved using a commercial application and the finite volume technique. To improve the dependability of the numerical findings, the computational model of the CTHX equipped with the CVP is verified. The numerical results are explained by streamlines in the CTHX, the local Nusselt number over the CTHX wall, and fluid temperature distributions. A summary is also provided for the dimensionless variables (averaged Nusselt number, friction factor, and thermal enhancement factor) of the CTHX with the CVP. The numerical results reveal that CVP insertion significantly enhances the heat transfer rate due to vortex flow generation. The maximum heat transfer rate is 15.29 times higher than that of a smooth circular tube, with the best thermal enhancement factor of 3.74 observed within our investigated range.
Keywords: Heat Transfer and Optimization; Heat Transfer Mechanisms; Heat Transfer and Boiling Studies